2007
DOI: 10.1007/s12020-007-9006-1
|View full text |Cite
|
Sign up to set email alerts
|

Genistein affects HER2 protein concentration, activation, and promoter regulation in BT-474 human breast cancer cells

Abstract: The HER2 proto-oncogene, a member of the epidermal growth factor receptor family, is overexpressed in 20-30% of breast cancers. Genistein, the main soy isoflavone, interacts with estrogen receptors (ER) and it is also a potent tyrosine kinase inhibitor. Previously, our laboratory found that genistein delayed mammary tumor onset in transgenic mice that overexpress HER2 gene. Our goal was to define the mechanism through which genistein affects mammary tumorigenesis in HER2 overexpressing mice. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…Sakla et al recently reported that genistein inhibits the protooncogene HER-2 protein tyrosine phosphorylation in breast cancer cells as well as delaying tumor onset in transgenic mice that overexpress the HER-2 gene This data support its potential anticancer role in chemotherapy of breast cancer [16]. However, effects independent of this activity have also been demonstrated [17].…”
Section: Biological Effects Of Genisteinmentioning
confidence: 84%
“…Sakla et al recently reported that genistein inhibits the protooncogene HER-2 protein tyrosine phosphorylation in breast cancer cells as well as delaying tumor onset in transgenic mice that overexpress the HER-2 gene This data support its potential anticancer role in chemotherapy of breast cancer [16]. However, effects independent of this activity have also been demonstrated [17].…”
Section: Biological Effects Of Genisteinmentioning
confidence: 84%
“…In vitro experiment demonstrated that genistein repressed tyrosine-specific protein kinase activity of EGFR, pp60 v-src , and pp110 gag-fes [24]. Genistein also inhibited the pro-oncogene HER2 protein tyrosine phosphorylation in breast cancer cells and delayed tumor onset in transgenic mice over-expressing HER2 gene [27]. Kim et al further showed that the phosphorylation of AKT and ERK was significantly downregulated by genistein after HeLa and CaSki cells were treated with genistein for 48 h [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed using a low micromolar (about 1 lM) concentration of genistein on BT-474 human BC cells (expressing only ERb), the molecule inhibited HER2 expression, phosphorylation and promoter activity throughout an ER-independent mechanism. When these cells were genetically transformed to express ERa, genistein mimicked E2 and inhibited HER2 protein phosphorylation (Sakla, Shenouda, Ansell, Macdonald, & Lubahn, 2007). In a different study, the authors documented an anti-proliferative and apoptotic effect of genistein and quercetin, using a canonical MCF-7 cell line and MCF-7 overexpressing HER2.…”
Section: Genistein As a Selective Protein Tyrosine Kinase Inhibitor: mentioning
confidence: 98%